The Last Temptation of Brian: From the Controversial Subversion to the Current Reflection - Dávila Vargas-Machuca, Miguel (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2021)
Biblical films have had widespread and repeated canons since the beginning of cinema, and films opposed to the prevailing film-religious dogma have generated excessive negative reactions. This text focuses on two significant examples of subversion of biblical cinema that addressed the figure of Christ in a new way away from those traditional canons. Their impact still resonates decades later, and this encourages reflection on both their approaches and the controversy. They aroused from a current perspective in which the moral conditioning of audio-visual works is unfortunately very much in evidence.